Convergencia hacia las normas internacionales de contabilidad para el sector público de los Gobiernos Autónomos Descentralizados - Pérez Arévalo, Jorge Luis (2023)
The International Public Sector Accounting Standards (NICSP), correspond to government accounting schemes, which require a special application in the type of information that must accompany the presentation of the Financial Statements. In Ecuador, the implementation of the International Accounting Standards for the Public Sector (NICSP), was adopted through the convergence method with the Government Accounting Standards through the Instructions for the convergence of the Government Accounting Standards to IPSAS from from January 1, 2020; With this, it seeks to contribute mainly with the principles that govern the Public Administration such as quality and transparency, enshrined in the Constitution of the Republic of Ecuador and that are related to the presentation of financial information..............